Real-world data in drug development strategies for orphan drugs: Tafasitamab in B-cell lymphoma, a case study for an approval based on a single-arm combination trial. Issue 6 (June 2022) - Serrano, Philippe; Yuen, Hiu Wah; Akdemir, Julia; Hartmann, Markus; Reinholz, Tatjana; Peltier, Sylvie; Ligensa, Tanja; Seiller, Claudia; Paraiso Le Bourhis, Achta
Graphical abstract: Highlights: Orphan drug approval strategies require specific ways to generate clinical evidence. Real-world data today may well support regulatory submissions of novel cancer drugs. Learn how individual patient data was used for hematological cancer drug approvals. Consider carefully the multiple methodological concerns and pitfalls when using RWD. Abstract : Tafasitamab (TAF) plus lenalidomide (LEN) is a novel treatment option for patients with relapsed/refractory diffuse large B-cell lymphoma (rrDLBCL) who are not eligible for autologous stem cell transplantation. The initial US/EU approvals for TAF represent precedents because this is the first time that approval of a novel combination therapy was granted based on a pivotal single-arm trial (SAT). Matching real-world data (RWD) helped to disentangle the contribution of individual agents. In this review, we present the TAF development strategy, the prospective incorporation of RWD within the clinical development plan, the corresponding regulatory hurdles of this strategy, and the prior regulatory actions for other cancer drugs that previously incorporated RWD and propensity score matching in EU and US regulatory submissions. We also outline how RWD could further advance and impact orphan drug development.